PCR-RFLP Based genetic diversity of Plasmodium vivax genotypes in district Mardan, Pakistan - Ullah,I. (2022)
Abstract Plasmodium vivax is the most common human malaria parasite in Asian countries including Pakistan. Present study was designed to explore the genetic diversity of plasmodium vivax genotypes based on Pvmsp-3α and Pvmsp-3βgenes using allelic specific nested PCR and RFLP assays markers from field isolates in district Mardan, Pakistan. Blood samples of 200 P. vivax malarial patients were collected after taking their written informed consent. Genetic diversity in nested PCR products was determined by Restriction Fragment Length Polymorphism (RFLP) utilizing Alu1 and PstI restriction enzymes for alpha and beta gene products digestion, respectively. For analysis the genetic diversity of the sub allelic variants of Pvmsp3α and Pvmsp3β genes, Chi-Square test was performed by utilizing Minitab programming software 18. The P value 0.05 was considered as statistically significant. For Pvmsp-3α genes after gel electrophoresis of digested products, four distinct genotypes were obtained from total of 50 samples; type A: 35 (70%) (1.5-2.0 kb), 12 of type B (24%) (1.5-1.7 kb), 2 of type C (4%) (0.5-1.5) and one for type D (2%) (0.5-0.65 kb) which could be characterized into 9 allelic pattern (A1-A4, B1-B3, C1, D), in which A3 remained the most predominant. For Pvmsp-3βgenes, three distinct genotypes were obtained from 50 samples; 40(80%) of type A (1.5-2.5 kb), 9 (18%) of type B (1.0-1.5kb) and 1(2%) of type C (0.65 kb) which could be characterized into 6 allelic patterns (A1-A3, B1-B2, and C1). Most dominant one in Type A was A1 alleles which were noted (46%), while in Type B, the most dominant were B1 (10%).This study is the first ever report of molecular epidemiology and genetic variation in Pvmsp-3α and Pvmsp-3β genes of P. vivax isolates by using PCR/RFLP from District Mardan and showed a remarkable level of genetic diversity in the studied genes of circulating parasites in the study area. The results of this study will contribute in future studies about the genetic structure of parasite and vaccine development against the malaria.